أهمية الاقتصاد الرقمي للدول العربية في ظل جائحة كورونا (كوفيد 19 ) وأثره على تحقيق التنمية المستدامة - - الاقتصاد الرقمي لدولة قطر نموذجا: The importance of digital economy for Arab countries in the light of Corona pandemic (Covid 19) and its impact on achieving sustainable development -Qatar’s digital economy as a model - عبد القادر زواتنية (Journal of North African Economies, 2025)
Abstract: This study aims to highlight the importance of digital economy for Arab countries in the light of Corona pandemic (Covid 19), and its role in achieving sustainable development in various fields, as the State of Qatar is one of the most prominent Arab models in the field of adopting a digital economy. The study found that the digital economy has a major role in mitigating the repercussions of the Corona pandemic on Arab economies, and it also has a significant impact on achieving sustainable development For Arab countries in the economic, social, and environmental fields, as Qatar has managed to achieve a high degree of digitization in each of the service sectors, agriculture, manufacturing, and non-manufacturing industries.